The Effect of Corporate Governance on Tax Avoidance with Profitability as Moderating Variable - Truly Wulandari; Arum Prastiwi; Sari Atmini (AIBPM Publisher, 2022)
This study aimed to examine and analyze the effect of corporate governance on tax avoidance through profitability as a moderating variable. This research is positive research using deductive reasoning by suggesting a theory which is then tested on a research design. The population in this study are companies listed on the Indonesia Stock Exchange from 2017-2021. Sample selection was made by using a purposive sampling method. The research results after testing 505 samples found that companies with good corporate governance tend not to do tax avoidance. Finally, this study provides empirical evidence regarding what factors can reduce the level of tax avoidance in companies by implementing good corporate governance. In addition, the researcher suggests that further research consider conducting cross-country comparative research because tax avoidance is not only a problem for Indonesia but also a global problem.